A Ti3C2Tx-carbon black-acrylic epoxy coating for 304SS bipolar plates with enhanced corrosion resistant and conductivity. (19th September 2022) - Yang, Beibei; Zhang, Guoli; Dong, Jiayu; Tang, Shaochun; Zhang, Lifang; Wu, Zhengguang; Bin, Duan; Song, Yaqiong; Lu, Hongbin
Abstract: A conducting and anticorrosive coating is crucial for the application of metal bipolar plates (BP) in proton exchange membrane fuel cell (PEMFC). In this work, a Ti3 C2 Tx (T)-carbon black (C)-acrylic epoxy (AE) coating is prepared on 304 stainless steel (SS) with enhanced corrosion resistance and conductivity. The corrosion resistance of the T-C-AE coating is investigated in a 0.5 M H2 SO4 solution as compared to the AE, T, and T-AE coatings. The T-C-AE coated 304SS exhibits the strongest corrosion resistance with the most positive corrosion potential and the lowest corrosion current density of 0.00673 μA cm −2 in all the samples, while retaining intact and compact surface morphology with the lowest metal ion dissolution even after immersed for 720 h. The addition of Ti3 C2 Tx and carbon black into the AE matrix greatly decreases interfacial contact resistance (ICR), and the T-C-AE coating achieves a low ICR of 15.5 mΩ cm −2 under 140 N cm −2 compaction force. The excellent anticorrosion performance is mainly attributed to the physical barrier and the cathodic protection provided by the stacked Ti3 C2 Tx (MXene) nanosheets in the T-C-AE coating. This eco-friendly, conducting, and anticorrosive T-C-AE coating has a good application prospect on SS BP of PEMFC. Graphical abstract: A waterborne Ti3 C2 Tx (T)-carbon black (C)-acrylic epoxy (AE) coating was prepared on 304 stainless steel (SS) with enhanced corrosion resistance and conductivity. Image 1 Highlights: A Ti3 C2 Tx (T)-carbon black (C)-acrylic epoxy (AE) coating is designed for the protection of 304 SS. The waterborne T-C-AE coating has enhanced corrosion resistance and conductivity. The Ti3 C2 Tx nanosheets provides barrier effect and cathodic protection for 304 SS. The interfacial contact resistance of T-C-AE is significantly decreased.